Distinguishing clinical characteristics of central nervous system tuberculosis in immunodeficient and non-immunodeficient individuals: a 12-year retrospective study - Woraseth Saifon; Khemajira Karaketklang; Anupop Jitmuang (BMC, 2023)
Abstract Background Central nervous system tuberculosis (CNS TB) is a severe Mycobacterium tuberculosis (MTB) infection. It is unclear whether a patient's immune status alters the clinical manifestations and treatment outcomes of CNS TB. Methods Between January 2007-December 2018, chart reviews of CNS TB, including tuberculous meningitis (TBM), tuberculoma/abscess, and TB myelitis, were made. Subjects were categorized as immunodeficient (ID) and non-immunodeficient (NID). Results Of 310 subjects, 160 (51.6%) were in the ID group-132 (42.6%) had HIV and 28 (9.0%) had another ID, and 150 (48.4%) were in the NID group. The mean age was 43.64 ± 16.76 years, and 188 (60.6%) were male. There were 285 (91.9%) TBM, 16 (5.2%) tuberculoma/abscess, and 9 (2.9%) myelitis cases. The TBM characteristics in the ID group were younger age (p = 0.003), deep subcortical location of tuberculoma (p = 0.030), lower hemoglobin level (p < 0.001), and lower peripheral white blood cell count (p < 0.001). Only HIV individuals with TBM had an infection by multidrug-resistant MTB (p = 0.013). TBM mortality was varied by immune status -HIV 22.8%, other ID 29.6%, and NID 14.8% (p < 0.001). Factors significantly associated with unfavorable outcomes in TBM also differed between the HIV and NID groups. Conclusions TBM is the most significant proportion of CNS TB. Some of the clinical characteristics of TBM, such as age, radiographic findings, hematological derangement, and mortality, including factors associated with unfavorable outcomes, differed between ID and non-ID patients.